Raw Semen Characteristics of Three Different Indonesian Local Roosters - Hambu, Emilia Kamung; Arifiantini, Raden Iis; Purwantara, Bambang; Darwati, Sri (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2016)
Indonesia has agreat variety of roosters, either indigenous type as well as exotic and cross breed. The purpose of this experiment was to study the characteristics of semen from three types of Indonesian local roosters such as Merawang, Kampung and crosses Sentul Kampung with Kedu (SK Kedu). A total of 15 roosters consist of Merawang roosters, Kampung, and SK Kedu roosters were 5 each. The semen was collected 3 times a week by dorso-abdominal and cloaca massage method. The parameters evaluation was macroscopic characteristics consist of volume, color, consistency, and pH. Microscopic evaluation of semen such as a mass movement, sperm motility, live sperm, sperm abnormality and sperm concentration. Results of this experiment showed that semen volume of Merawang (0.40±0.26 mL) was higher (p<0.05) compare to Kampung (0.24±0.12 mL) or SK Kedu (0.16±0.10 mL) but no difference on semen color, consistency and semen pH. There were no difference in the mass movement, sperm motility and live sperm as well as on sperm abnormality among three types of roosters. Sperm concentration of Merawang (4490 million mL-1) was significantly higher than Kampung (3245 million mL-1) and the SK Kedu roosters (3751 million mL-1). Its was conclude that Merawang roosters had good semen quality better than Kampung and SK Kedu roosters